2021
DOI: 10.24198/jkp.v9i3.1709
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Knowledge and Behaviours of Indonesian Health Care Providers toward the Prevention of COVID-19

Abstract: Background: Due to the high risk of exposure of health care providers (HCPs) at the forefront of the COVID-19 responses, their knowledge and prevention behaviors towards COVID-19 have become crucial parts of their job performances.Purpose: This study aims to identify the level of knowledge and prevention behaviors of  HCPs toward COVID-19 and factors associates.Methods: This study utilized a cross-sectional research design. The samples consisted of 182 HCPs in Malang, East Java Province, Indonesia. The data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Many coping mechanism can be utilized (Angelica & Tambunan, 2021). One strategy to reduce stress related to COVID-19 is to get more information and to be updated with COVID-19 itself (Prasetyo, Setyamardina, Rahayu, & Huriah, 2021). It has been found that stress and anxiety are related with knowledge level.…”
Section: Discussionmentioning
confidence: 99%
“…Many coping mechanism can be utilized (Angelica & Tambunan, 2021). One strategy to reduce stress related to COVID-19 is to get more information and to be updated with COVID-19 itself (Prasetyo, Setyamardina, Rahayu, & Huriah, 2021). It has been found that stress and anxiety are related with knowledge level.…”
Section: Discussionmentioning
confidence: 99%